Is there relationship between pectoralis minor muscle length and shoulder rotator muscles strength? - Kocahan, T.; Akinoglu, B.; Soylu, C.; Coban, Ö.; Ün Yildirim, N. (Universal Journal of Public Health, 2018)
Problem Statement: In joint movement, agonist and antagonist muscle strength, as well as the length and the shortness of these muscles is an important parameter. Muscle shortness is one of the factor that responsible of sports injuries. Shoulder is one of the most injured joint in Judo. In this joint, determination of the relationship between muscle shortness and agonist-antagonist muscles strength will be effective to increase muscle strength, sportive performance and prevent sports injuries. Purpose of Study: This study was conducted to determine the relationship between pectoralis minor (PM) muscle length and shoulder internal(IR)/external(ER) rotation isokinetic muscle strength in Judo athletes. Methods: The study included 80 (56 males, 24 female) professional Judo athletes aged between 14-25 (mean 17,31±2,51). Isokinetic muscle strength was assessed by ISOMED 2000® device. Pectoralis minor length was evaluated using a flexible tape measure in resting position. The assessments were made bilaterally. Findings and Results: There was a strong and statistically significant correlation between the PM length and the shoulder IR and ER peak torque values at both angular velocities and both sides (p <0,01). Conclusions and Recommendations: It was determined that the relationship between the length of the PM muscle and the internal and external rotator muscle strength of Judo athletes. Therefore, we think that by increasing shoulder muscle strength to enhance sportive performance, stretching exercises for PM muscle shortening should be added to training programs.